Reflux and Barrett’s disease: revival of endoscopic antireflux procedures? - Bisschops, R. (Endoscopy, 2013)
After the initial enthusiasm at the end of the previous century, interest in endoscopic anti-reflux procedures decreased due to inefficiency or complications with devices, a lack of good clinical trials, or financial problems of the manufacturers. In 2012 some interesting results on new and old devices have been published.